1999
DOI: 10.1093/jn/129.7.1269
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol, the Major Olive Oil Biophenol, Protects Against Oxidized-LDL-Induced Injury in Caco-2 Cells

Abstract: Experimental and clinical evidence suggest that oxidative stress causes cellular damage, leading to functional alterations of the tissue. Free radicals may thus play an important role in the pathogenesis of a number of human diseases. Among pro-oxidant agents, oxidized LDL lead to the production of cytotoxic reactive species, e.g., lipoperoxides, causing tissue injury and various subsequent pathologies including intestinal diseases. Thus, to analyze the oxidative damage induced by oxidized LDL to intestinal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 35 publications
3
87
0
6
Order By: Relevance
“…The enzymes degrade the polysaccharides and liberate phenolic antioxidants, which, after equilibrium, are distributed among three phases: oil, water and solid. Antioxidants are sensitive to oxidation during malaxation of the olive paste and the nitrogen atmosphere protects them against oxidative destruction (Gutiérrez et al, 1977;Giovannini et al, 1999). In general the native enzymes present in the olive fruit are deactivated during the oil extraction process or crushing step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes degrade the polysaccharides and liberate phenolic antioxidants, which, after equilibrium, are distributed among three phases: oil, water and solid. Antioxidants are sensitive to oxidation during malaxation of the olive paste and the nitrogen atmosphere protects them against oxidative destruction (Gutiérrez et al, 1977;Giovannini et al, 1999). In general the native enzymes present in the olive fruit are deactivated during the oil extraction process or crushing step.…”
Section: Discussionmentioning
confidence: 99%
“…The virgin olive oil, apart from the oily phase (fatty acids) contains precious substances of high biological value such as phenols, ortho-diphenols and various natural antioxidants, tocopherol (Vitamin E), flavones as well as a high content of oleic acid, alcohols, sterols, chlorophyll, volatile aromatic substances, etc. (Baldioli et al, 1996;Giovannini et al, 1999;Iconomou et al, 2005;De Faveri et al, 2008). This fact leads to health claims, particularly regarding children, concerning the prevention of cardiovascular and gastrointestinal diseases, the deceleration of ageing and cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…OxLDL generally induce progressive alterations of cell morphology leading to either apoptosis or necrosis in several cultured cells [31,32]. The role of ROS in oxLDL-mediated cytotoxicity has been recently reported, in particular through the activation of the caspase cascade [26,33] and the depletion of glutathione and its related enzymes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The F values from the one-way ANOVA statistics for the formation of tyrosol, tryptophol, and phenylethanol shown on Table 1 further support the significance of nutrient supplements as well as the significant influence of yeast strains on the production of the three phenolic compounds. The multivariate analysis of variance also revealed that there is an overall significant influence of yeast strain on the production of tyrosol, tryptophol, and phenylethanol (Wilks' λ = 0.1377, F (3,14) = 29.23, P < 0.05) and a significant difference between control, TTPaa, No Kiwi control, and Kiwi samples on the production of the phenolic components (Wilks' λ = 0.0075, F (9,34) = 24.54, P < 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…These phenolic compounds have significant applications in food and beverage manufacturing including wine-making. Ty-rosol, found abundantly in olive oil, is a natural phenolic compound known to have high anti-oxidative properties [3] [4]. Samuel et al [5] observed that tyrosol treatment in animals significantly reduced heart cell death as a result of protective signaling from Akt, eNOS, FOXO3a, and induced expression of the longevity protein SIRT1 in the heart.…”
Section: Introductionmentioning
confidence: 99%